Unidirectional Growth of Microbumps on (111)-Oriented and Nanotwinned Copper - Hsiao, Hsiang-Yao; Liu, Chien-Min; Lin, Han-wen; Liu, Tao-Chi; Lu, Chia-Ling; Huang, Yi-Sa; Chen, Chih; Tu, K. N. (Science (American Association for the Advancement of Science), 2012)
One challenge in moving to three-dimensional integrated circuit architectures is the need for aligned interconnects to join neighboring layers. Hsiao et al. (p. 1007 ) applied rapid stirring to the direct current electroplating of copper to produce films with oriented copper grains that have a high density of nanotwin defects. The resulting material was an excellent platform for the growth of copper-tin intermetallic compounds in the form of arrays of microbumps potentially suitable for the soldering of electronic components. Oriented copper grains grown using direct-current electroplating serve as a template for intermetallic microbumps. Highly oriented [111] Cu grains with densely packed nanotwins have been fabricated by direct-current electroplating with a high stirring rate. The [111]-oriented and nanotwinned Cu (nt-Cu) allow for the unidirectional growth of Cu 6 Sn 5 intermetallics in the microbumps of three-dimensional integrated-circuit packaging; a uniform microstructure in a large number of microbumps of controlled orientation can be obtained. The high-density twin boundaries in the nt-Cu serve as vacancy sinks during the solid-state reaction between Pb-free solder and Cu and greatly reduce the formation of Kirkendall (or Frenkel) voids.